A modified epoxy-cerium oxide polishing liquid and preparation method thereof

By introducing epoxy carboxylic acid groups and adding stabilizers to the surface of cerium oxide, the polishing rate and suspension stability problems of traditional cerium oxide polishing materials are solved, achieving a more efficient polishing effect and a longer service life.

CN119144237BActive Publication Date: 2025-02-14INNER MONGOLIA UNIVERSITY

Patent Information

Application Number
CN202411663761.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

During the use of traditional cerium oxide polishing materials, the balance between polishing rate and surface defects is difficult to control, and the suspension stability is poor, affecting the uniformity of polishing.

Method used

By introducing epoxy carboxylic acid groups on the surface of cerium oxide, the dispersion and chemical stability of the abrasive are enhanced, and stabilizers and pH adjusters are added to improve suspension stability.

Benefits of technology

It improves the chemical stability and suspension stability of cerium oxide, extends the service life of the abrasive, and ensures polishing efficiency and surface finish.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144237B_ABST
    Figure CN119144237B_ABST
Patent Text Reader

Abstract

The invention provides a modified epoxy-cerium oxide polishing liquid and a preparation method thereof, which is mainly prepared from the following raw materials by mass percentage: 0.2%-0.5% of modified cerium oxide abrasive; 0.02%-0.35% of stabilizer; 0.25%-0.4% of ammonia water; 99.08%-99.2% of deionized water; wherein the modified cerium oxide abrasive is cerium oxide and epoxy carboxylic acid mixed in a mass ratio of (20:1)-(200:1). The epoxy-cerium oxide polishing liquid can make the abrasive more evenly dispersed in the solution, improve the uniformity of the suspension; and maintain its suspension (D50) for up to 2 months under the condition of ensuring the removal rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth materials, in particular to a modified epoxy-cerium oxide polishing liquid and a preparation method thereof. Background Art

[0002] In the silicon wafer manufacturing process, chemical mechanical polishing (CMP) is a crucial technology used to achieve surface flatness to meet the requirements of high-precision and high-density integration of semiconductor devices. As a key polishing material, cerium oxide (CeO2) has been widely used in the silicon wafer polishing process due to its unique physical and chemical properties.

[0003] The polishing effect of cerium oxide mainly comes from its excellent chemical reactivity and mechanical polishing ability. During the polishing process, cerium oxide particles can form an oxide layer through chemical reaction with the silicon surface, and remove the oxide layer through mechanical friction, thereby achieving a flattening effect. In addition, the particle structure of cerium oxide can provide a higher polishing rate and a lower defect generation rate, which can improve polishing efficiency while ensuring flatness.

[0004] However, there are some problems in the application of traditional cerium oxide polishing materials, such as the difficulty in controlling the balance between polishing rate and surface defects, the tendency of particle agglomeration during use, and poor suspension stability, which affects the uniformity of polishing. Therefore, how to improve the preparation process, surface modification or dispersion technology of cerium oxide particles to ensure its removal rate while improving its suspension stability has become a hot topic in current research.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a modified epoxy-cerium oxide polishing liquid, which introduces epoxy carboxylic acid groups on the surface of cerium oxide to enhance the dispersibility and chemical stability of the abrasive, enhance the chemical stability of cerium oxide, reduce the dissolution or passivation of particles caused by chemical reactions during the polishing process, and extend the service life of the abrasive; at the same time, by adding stabilizers and pH adjusters, it is ensured that the suspension stability is further improved without affecting its removal rate.

[0007] The second purpose of the present invention is to provide a method for preparing the above-mentioned modified epoxy-cerium oxide polishing liquid, which can make the particle size of the prepared cerium oxide more uniform, which is convenient for the modification of epoxy carboxylic acid groups; at the same time, the preparation steps are simple, which significantly saves manufacturing costs and is convenient for mass production; at the same time, the preparation process is green, reduces environmental pollution, and is more in line with the requirements of green chemistry.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention provides a modified epoxy-cerium oxide polishing liquid, which is mainly prepared from the following raw materials in terms of mass percentage:

[0010] Modified cerium oxide abrasive 0.2%-0.5%;

[0011] Stabilizer 0.02%-0.35%;

[0012] Ammonia 0.25%-0.40%;

[0013] Deionized water 99.08%-99.2%;

[0014] The modified cerium oxide abrasive is a mixture of cerium oxide and epoxy carboxylic acid in a mass ratio of (20:1) to (200:1).

[0015] In the present invention, epoxy carboxylic acid is used to modify cerium oxide abrasives. The carboxyl group of epoxy carboxylic acid can form a weak chemical bond with the polishing surface, thereby increasing the interaction between cerium oxide and the silicon surface (the object to be polished), and further improving the polishing rate and surface finish. The cerium oxide abrasive modified with epoxy carboxylic acid groups has stronger dispersibility, which helps to reduce the agglomeration of particles in the polishing liquid, thereby ensuring the uniformity of the abrasive during the polishing process and reducing surface defects; in addition, the modification can also improve the chemical stability of cerium oxide, reduce the dissolution or passivation of particles caused by chemical reactions during the polishing process, and extend the service life of the abrasive.

[0016] A small amount of stabilizer can eliminate the foam generated during the preparation process, increase the viscosity of the polishing liquid, improve its suspension stability, and ensure the polishing efficiency of the product; at the same time, it can assist epoxy carboxylic acid in stabilizing the cerium oxide abrasive, reduce the occurrence of surface defects, and significantly improve the quality and flatness of the silicon wafer surface after polishing with the polishing liquid, meeting the needs of high-precision manufacturing processes.

[0017] In the present invention, the mass ratio between epoxy carboxylic acid and cerium oxide is limited. It is found through experiments that when epoxy carboxylic acid is used to modify and connect cerium oxide, a 1:1 connection between the modifier and cerium oxide cannot be achieved; that is, due to the influence of steric hindrance or electrostatic repulsion, epoxy carboxylic acid cannot modify all cerium oxide contained in the system, but can only partially modify it. Therefore, it is necessary to find the optimal ratio between the modifier and cerium oxide in the modification process to achieve the optimal modification effect.

[0018] Through the adjustment of the experiment, it was found that when cerium oxide and epoxy carboxylic acid were mixed in a mass ratio of (20:1)-(200:1), especially when the content of cerium oxide was a multiple of the content of epoxy carboxylic acid, although only part of the performance of cerium oxide changed, there was an intermolecular force between the modified cerium oxide abrasive particles and the ordinary cerium oxide abrasive particles, which could reduce the aggregation tendency between cerium oxide particles and enable the abrasive to be dispersed evenly in the system for a long time, thereby achieving the change of the physical and chemical properties of the polishing liquid. When the mass of epoxy carboxylic acid is large, it not only fails to improve the efficiency of the connection between cerium oxide and the modifier, resulting in waste, but also may affect the physical and chemical properties of cerium oxide. In the case of excessive cerium oxide, the content of modified cerium oxide is too small, resulting in reduced dispersion performance and inability to disperse stably for a long time.

[0019] Preferably, as a further specific implementation, the mass ratio of the cerium oxide to the epoxycarboxylic acid is (40:1)-(100:1).

[0020] Preferably, as a further specific implementation, the mass ratio of the cerium oxide to the epoxycarboxylic acid is 100:1 or 50:1.

[0021] As mentioned above, the polishing liquid prepared under the condition that the content of cerium oxide is a multiple of the content of epoxy carboxylic acid has better performance. Through further experimental screening, it is found that in the range of (20:1)-(200:1), the performance of the polishing liquid is more obvious in the range close to 100:1 and 50:1. Therefore, in the actual preparation process, the mass ratio of cerium oxide to epoxy carboxylic acid = 100:1 or 50:1 can not only effectively guarantee the performance of the final polishing liquid, but also avoid waste.

[0022] Preferably, as a further specific implementation, the particle size of the cerium oxide is 200nm-400nm.

[0023] The polishing performance of cerium oxide abrasive is highly dependent on its own size and shape. The chemical polishing performance of the oxide increases monotonically with the particle size of the cerium oxide abrasive. Therefore, in the selection of cerium oxide particle size, large-particle cerium oxide particles are more inclined to be selected as the raw material for the reaction; but considering the steric hindrance or the interaction force between molecules, the actual selection of cerium oxide particle size should not be too large or too small, otherwise it will affect the dispersion performance of the final prepared polishing liquid.

[0024] Preferably, as a further specific embodiment, the epoxycarboxylic acid is a mixture of any one or more of cis-epoxysuccinic acid, oxirane formic acid, 2,3-epoxyethylene dicarboxylic acid or trans-epoxysuccinic acid;

[0025] The stabilizer is a mixture of one or more of polyvinyl alcohol, polyethylene glycol, polydimethylsiloxane, polyethylene oxide, polypropylene oxide, carboxymethyl cellulose, sodium polyacrylate or hydroxyethyl methyl cellulose.

[0026] The principle of polishing liquid is to form Ce-O-Si bond. Some polishing abrasives currently known in the market will introduce metal ions and oxidants during the preparation process. Oxidants can form Ce-O-Si bonds. 3+ Oxidation to Ce 4+ , and Ce 4+ It has better polishing performance; while metal ions may destroy the formed Ce-O-Si bond during the polishing process, reducing the polishing performance. Therefore, although the introduction of metal ions and oxidants can improve the polishing performance, it is speculated that due to the negative impact of metal ions on Ce-O-Si bonds, some physical properties of the prepared polishing liquid are difficult to break through.

[0027] In the present invention, the selected epoxy carboxylic acid and stabilizer can achieve the modification of cerium oxide without introducing metal ions, thereby reducing the influence of metal ions on the polishing performance of the formed polishing liquid; at the same time, the stabilizer can effectively improve other physical properties of the polishing liquid while ensuring that its polishing performance is not affected.

[0028] Preferably, as a further specific embodiment, the epoxycarboxylic acid is a mixture of cis-epoxysuccinic acid and epoxyethylcarboxylic acid in a mass ratio of (1-3):1;

[0029] The stabilizer is polyvinyl alcohol, polydimethylsiloxane and carboxymethyl cellulose mixed in a mass ratio of (1-3): 1:1.

[0030] Preferably, as a further specific embodiment, the cis-epoxysuccinic acid and epoxyethyl formic acid are mixed in a mass ratio of 1:1;

[0031] The stabilizer is a mixture of polyvinyl alcohol, polydimethylsiloxane and carboxymethyl cellulose in a mass ratio of 2:1:1.

[0032] The experimental results show that when epoxycarboxylic acid is cis-epoxysuccinic acid and epoxyethyl formic acid mixed in a mass ratio of (1-3):1, preferably 1:1, it is more conducive to improving the performance of the polishing liquid. It is speculated that it may be the influence of the intermolecular interaction force, thereby increasing the modification effect. When polyvinyl alcohol, polydimethylsiloxane and carboxymethyl cellulose are mixed in a mass ratio of (1-3):1:1, the polishing liquid can be defoamed, thickened and stabilized. When the three are mixed in a mass ratio of 2:1:1, the suspension stability and dispersibility of the polishing liquid can be better guaranteed.

[0033] Preferably, as a further specific embodiment, the pH adjuster is aqueous ammonia.

[0034] In the present invention, since no metal ions are introduced during the reaction, pH regulators containing metal ions are not selected; although ammonia gas dissolving in water will produce NH4 + Ions, but the metal ions have little effect on the physical properties of the polishing liquid, and the metal ions are easily eliminated. During the preparation process, the polishing agent system needs to be adjusted to an alkaline environment of pH = 10-12 to improve its suspension stability.

[0035] The present invention also provides a method for preparing the modified epoxy-cerium oxide polishing liquid, comprising:

[0036] preparing cerium oxide, and mixing the cerium oxide with deionized water to form a uniform slurry;

[0037] Grinding the slurry to obtain a grinding medium, and freeze-drying the grinding medium to obtain a cerium oxide abrasive;

[0038] The polishing abrasive is dispersed in deionized water, subjected to ultrasonic vibration, epoxy carboxylic acid is added, mixed, heated, centrifuged, washed, and freeze-dried to obtain a modified epoxy-cerium oxide abrasive;

[0039] The epoxy-cerium oxide abrasive is mixed with deionized water, a pH regulator and a stabilizer are added, and ultrasonic dispersion is performed to obtain the abrasive.

[0040] When cerium oxide is mixed with deionized water to form a slurry, the water content thereof needs to be properly controlled. In this step, the amount of water added is generally 3-5 times the mass of the cerium oxide abrasive to ensure good fluidity and dispersibility.

[0041] The drying method used in the present invention is freeze drying, which can not only ensure the drying efficiency, but also facilitate the grinding of the abrasive prepared. Adding a pH regulator and a stabilizer at the end of the reaction is conducive to the long-term storage of the polishing liquid and can improve its dispersibility and suspension stability.

[0042] Preferably, as a further specific embodiment, the freeze-drying temperature is -30°C to (-20°C);

[0043] The heating temperature is 70°C-100°C.

[0044] Under the condition of this solid content, it is more conducive to the dispersion of modified epoxy-cerium oxide in ionized water. The optimal heating temperature is 80℃ and the optimal heating time is 12h.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] By modifying epoxy carboxylic acid and adding stabilizers, the chemical and physical properties of cerium oxide abrasives can be optimized, which can improve the reactivity and removal rate in the chemical mechanical polishing process, thereby effectively improving the polishing efficiency; by interacting with the surface of cerium oxide particles, a stable surface modification layer is formed, which reduces the aggregation tendency between particles, enables the abrasive to be more evenly dispersed in the solution, and improves the uniformity of the suspension; the surface has hydrophilic groups, which increases the solubility of the particles in the solution and reduces the particle sedimentation rate, thereby prolonging the stability time of the suspension.

[0047] The modified cerium oxide nano-abrasive prepared by the preparation method of the present invention can maintain its suspension (D50) for up to 2 months without any additives and with guaranteed removal rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 : X-ray diffraction image of epoxycarboxylic acid modified cerium oxide abrasive;

[0049] Figure 2 :Thermogravimetric analysis images of epoxycarboxylic acid modified cerium oxide abrasives;

[0050] Figure 3 : Transmission electron microscopy image of epoxycarboxylic acid modified cerium oxide abrasive;

[0051] Figure 4 : Scanning electron microscope image of epoxy carboxylic acid modified cerium oxide abrasive;

[0052] Figure 5 :Photo of 1h suspension stability of epoxycarboxylic acid modified cerium oxide abrasive;

[0053] Figure 6 : Photo of 7-day suspension stability of epoxycarboxylic acid modified cerium oxide abrasive;

[0054] Figure 7 :Photo of 15-day suspension stability of epoxycarboxylic acid modified cerium oxide abrasive;

[0055] Figure 8 : Photograph of 30-day suspension stability of epoxycarboxylic acid modified cerium oxide abrasive. DETAILED DESCRIPTION

[0056] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0057] Example 1

[0058] Step 1: Preparation of cerium oxide

[0059] 2000 g of cerium carbonate was calcined at 600°C in a rotary kiln for 24 h, and then ground to obtain cerium oxide with a particle size of 300 nm.

[0060] Step 2: Modification

[0061] The prepared cerium oxide is mixed with deionized water 5 times its own weight to form a uniform slurry; the cerium oxide slurry is evenly added into the grinding chamber of the sand mill, and the grinding medium is filtered and separated to obtain a uniform and fine dispersion. The dispersion is placed in a freeze dryer at -30°C for freeze drying, and then ground with a mortar to obtain a cerium oxide abrasive.

[0062] 5 g of cerium oxide abrasive, 0.05 g of a mixture of cis-epoxysuccinic acid and 0.05 g of epoxyethyl formic acid, and 100 mL of water were mixed in a 250 mL round-bottom flask and placed in a stirrer with oil bath heating. When the oil bath temperature reached 80 °C, the timing was started. After reacting for 12 h, the solid obtained by centrifugation was washed with deionized water and anhydrous ethanol, freeze-dried at -20 °C, and ground to obtain a modified epoxy-cerium oxide abrasive (such as Figure 1-Figure 4 As shown, the X-ray diffraction image, thermogravimetric analysis image, transmission electron microscope image and scanning electron microscope image of the modified epoxy-cerium oxide abrasive are clearly shown).

[0063] Step 3: Prepare the polishing solution

[0064] The above 2.5 g modified epoxy-cerium oxide abrasive and 500 g deionized water were mixed, 2 g ammonia water was added dropwise to adjust the pH to 11.5, and a mixture of 0.05 g polyvinyl alcohol, 0.025 g polydimethylsiloxane and 0.025 g carboxymethyl cellulose was added at the same time. After ultrasonic dispersion for 60 min, stirring was performed for 30 min to obtain a polishing liquid prepared with the abrasive.

[0065] The contents of various substances prepared under this condition are shown in Table 1:

[0066] Table 1: Mass and percentage of each substance

[0067] .

[0068] Configuration of cerium oxide abrasive suspension and its suspension test:

[0069] Accurately weigh 1.5g of cerium oxide sample (weighed to 0.0001g), place it in a 150mL beaker, add a little water to make pulp, add 30mL-40mL of water, transfer to a 50mL graduated flask, and dilute to the scale with water. Transfer it to a beaker, place it on an electric magnetic stirrer, stir it at room temperature for 10min, then transfer it to a cylindrical separatory funnel, let it stand at room temperature for 4 hours before use. Take 0.5g-1.0g of powder sample and place it in a 50mL beaker filled with 10mL deionized water, ultrasonically disperse it in a water bath ultrasonic tank (add an appropriate amount of water to the ultrasonic tank in advance, and the amount of water should just immerse the sample solution in the beaker) for 20min, and measure immediately.

[0070] After standing for 4 hours, use a pipette to draw 5 mL of suspension from about 6 mL below the liquid level on the top of the cylindrical separatory funnel, transfer it into a 200 mL volumetric flask and dilute it to the mark with water. Then open the piston all the way and put about 10 mL of the lower suspension into a 50L beaker, use a pipette to draw 5 mL of it into a 200 mL volumetric flask, and dilute it to the mark with water. Shake the above two samples evenly, use a pipette to draw the required milliliters each and transfer them to a 50 mL volumetric flask, and dilute it to the mark with an acetone-water mixture. Continue until the measured value is 50% of the initial value, and record the time at this time.

[0071] Example 2

[0072] The specific implementation method is the same as that of Example 1, except that the type of epoxycarboxylic acid is changed: cis-epoxysuccinic acid, epoxyethylcarboxylic acid, 2,3-epoxyethylenedicarboxylic acid, and trans-epoxysuccinic acid.

[0073] When epoxycarboxylic acid was not used, a CeO2 sample was obtained;

[0074] When cis-epoxysuccinic acid was used, sample No. 1 was obtained;

[0075] When oxirane formic acid was used, sample No. 2 was obtained;

[0076] When 2,3-ethylene oxide dicarboxylic acid was used, sample No. 3 was obtained;

[0077] When trans-epoxysuccinic acid was used, sample No. 4 was obtained;

[0078] When the mass ratio of cis-epoxysuccinic acid to epoxyethyl formic acid was 3:1, sample No. 5 was obtained;

[0079] When the mass ratio of cis-epoxysuccinic acid to epoxyethyl formic acid was 5:1, sample No. 6 was obtained;

[0080] When the mass ratio of cis-epoxysuccinic acid to epoxyethyl formic acid is 0.5:1, sample No. 7 is obtained.

[0081] The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 2.

[0082] Table 2: Effect of different epoxy carboxylic acids on the suspension properties of polishing liquid

[0083] .

[0084] It can be seen from the experimental results that different epoxy carboxylic acids have an important influence on the suspension stability of the modified cerium oxide nanoabrasive suspension. Among them, the suspension stability is best when the mass ratio of cis-epoxysuccinic acid to epoxyethyl formic acid is 1:1, followed by cis-epoxysuccinic acid. When cis-epoxysuccinic acid is excessive or the content is low, it will cause a slight decrease in suspension stability; based on the experimental results, the mass ratio of cis-epoxysuccinic acid to epoxyethyl formic acid is 1:1 as the best ratio. The above-mentioned epoxy carboxylic acids can be chemically bonded to the surface hydroxyl groups of cerium oxide after surface hydroxylation, thereby greatly improving the suspension stability and ensuring its excellent removal rate. The principle of improving the stability of cerium oxide abrasives by compounding cis-epoxysuccinic acid and epoxyethyl formic acid is speculated to be the effect of intermolecular forces on cerium oxide.

[0085] Example 3

[0086] Specific implementation method The method is the same as Example 1, except that the ratio of epoxy carboxylic acid to cerium oxide nanoabrasive is changed.

[0087] In this embodiment, epoxycarboxylic acid is prepared by mixing cis-epoxysuccinic acid and epoxyethylcarboxylic acid in a mass ratio of 1:1, hereinafter referred to as CES; and finally a polishing liquid CeO2@CES is obtained.

[0088] When the mass ratio of cerium oxide to epoxy carboxylic acid = 200:1, 5g cerium oxide and 0.025g CES were used;

[0089] When the mass ratio of cerium oxide to epoxy carboxylic acid = 100:1, 5g cerium oxide and 0.05g CES were used;

[0090] When the mass ratio of cerium oxide to epoxy carboxylic acid = 50:1, 5 g cerium oxide and 0.1 g CES were used (Example 1);

[0091] When the mass ratio of cerium oxide to epoxy carboxylic acid = 40:1, 5g cerium oxide and 0.125g CES were used;

[0092] When the mass ratio of cerium oxide to epoxy carboxylic acid = 20:1, 5g cerium oxide and 0.4g CES were used;

[0093] The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 3.

[0094] Table 3: Effect of different mass ratios of cerium oxide and epoxy carboxylic acid on the performance of polishing liquid

[0095] .

[0096] It can be seen from the experimental data of Example 3 that at a higher CES to cerium oxide mass ratio (such as 100:1), the surface of cerium oxide is covered by more CES molecules, thereby providing more negative charge or functional group sites. This higher charge density can effectively enhance the electrostatic repulsion between particles, thereby reducing particle aggregation and improving the stability of the suspension. At the same time, CES molecules contain certain hydrophobic components, and a stronger hydrophobic change may occur with the surface of cerium oxide. This change can inhibit the agglomeration of particles and make the particles more evenly dispersed in the aqueous solution, thereby improving the suspension stability.

[0097] Example 4

[0098] Detailed Description of the Invention The method is the same as in Example 1, except that only the particle size of cerium oxide is changed.

[0099] Solution 1: Select the particle size of cerium oxide to be 200 nm;

[0100] Option 2: Select the particle size of cerium oxide to be 300nm

[0101] Solution 3: Select the particle size of cerium oxide to be 400 nm.

[0102] The experimental results are shown in Table 4.

[0103] Table 4: Effect of different particle sizes of cerium oxide on polishing performance and suspension stability of polishing liquid

[0104] .

[0105] It can be seen from the experimental data that under appropriate conditions, the particle size of cerium oxide can ultimately ensure that the polishing rate of the final polishing liquid is moderate and there are no obvious scratches. At the same time, larger or smaller particle sizes may lead to a decrease in its suspension stability.

[0106] Example 5

[0107] The specific implementation steps are consistent with those in Example 1, except that the oil bath stirring heating temperature and heating time during the modification process are changed.

[0108] The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 5.

[0109] Table 5: Effect of different heating temperatures and heating times on the suspension stability of the polishing liquid

[0110] .

[0111] It can be seen from the experimental data of Example 5 that different heating temperatures and heating times have an important influence on the suspension stability of the polishing liquid. At a lower temperature (such as 60 degrees), the reaction rate may be slower, the modification effect of epoxy carboxylic acid on the surface of cerium oxide is not sufficient, and the suspension improvement effect is not obvious. At a higher temperature (such as 100 degrees), although the reaction speed is faster, it may cause the molecular structure of epoxy carboxylic acid to change or produce side reactions, affecting the modification effect, resulting in a decrease in suspension.

[0112] The longer the reaction time, the more time the epoxy carboxylic acid is in contact with the cerium oxide surface, and the more complete the modification. However, if the reaction time exceeds a certain time, over-modification may occur, resulting in increased surface instability and affecting the stability of the suspension. In this experiment, 12 hours is a moderate time for epoxy carboxylic acid to form a stable modification layer on the cerium oxide surface and achieve the best effect.

[0113] Example 6

[0114] The specific implementation method is consistent with Example 1, and only the mass of each substance is changed to change the percentage content. The specific changes are shown in Table 6.

[0115] Table 6: Effect of the change in the proportion of each substance on the suspension stability of the polishing liquid

[0116] .

[0117] It can be seen from the data in Example 6 that the change in the proportion will have a certain impact on the suspension stability of the polishing liquid. Specifically, the suspension stability of the polishing liquid has decreased. The main reason is that the proportion of the modified cerium oxide abrasive has decreased, which has caused the proportion of the modified cerium oxide abrasive to decrease to a certain extent, thereby reducing its performance. But in general, the change in its performance is within the expected range.

[0118] Comparative Example 1

[0119] The specific implementation method is consistent with Example 1, except that the mass ratio of cerium oxide to epoxy carboxylic acid mixture is changed:

[0120] When the mass ratio of cerium oxide to epoxy carboxylic acid = 250:1, 5 g cerium oxide and 0.02 g CES were used;

[0121] When the mass ratio of cerium oxide to epoxy carboxylic acid is 10:1, 5 g of cerium oxide and 0.5 g of CES are used.

[0122] The specific experimental results are shown in Table 7.

[0123] Table 7: Effect of different mass ratios of cerium oxide and epoxy carboxylic acid on the performance of polishing liquid

[0124] .

[0125] By comparing the experimental data of Comparative Example 1 with that of Example 3, it can be seen that when the mass ratio of cerium oxide to epoxycarboxylic acid is too large or too small, the suspension stability will be reduced; no matter which substance is excessive, the connection efficiency between cerium oxide and epoxycarboxylic acid will be reduced, which will cause the components in the prepared polishing liquid to easily aggregate, thereby reducing its dispersion performance.

[0126] Comparative Example 2

[0127] The polishing liquid was prepared by mixing cerium oxide and an oxidant. The specific implementation method was consistent with Example 1, and only the mass ratio of cerium oxide to the oxidant was changed:

[0128] The oxidant used in this embodiment is hydrogen peroxide.

[0129] When the mass ratio of cerium oxide to oxidant = 10:1, 5g cerium oxide, 0.5g hydrogen peroxide, and 0.5g CES were used;

[0130] When the mass ratio of cerium oxide to oxidant = 20:1, 5 g of cerium oxide, 0.25 g of hydrogen peroxide, and 0.25 g of CES were used.

[0131] The specific experimental results are shown in Table 8.

[0132] Table 8: Effect of different mass ratios of cerium oxide and oxidant on the performance of polishing liquid

[0133] .

[0134] Experimental data show that the addition of an oxidant will have a significant impact on the suspension of CeO2 nanoparticles in the polishing solution. At the same time, the addition of an oxidant will react with the epoxy carboxylic acid used for modification, resulting in a weakening of the modification effect.

[0135] Experimental Example 1: Determination of polishing rate of polishing liquid

[0136] Using samples 1-7 in Example 2 and the modified epoxy-cerium oxide abrasive prepared in Example 1, 2.5 g was evenly dispersed in 500 mL of deionized water, and the polishing liquid was prepared after 30 minutes of ultrasound. The experimental results of the polishing rates of samples 1-7 and CeO2 in Example 2 correspond to those of 1-7 and CeO2 in this experimental example. The above samples were used to polish 1 mm thick SiO2 sheets. For the abrasive samples modified with different epoxy carboxylic acids, the specific polishing rates are shown in Table 9.

[0137] Table 9: Effect of different epoxy carboxylic acid modifications on the polishing rate of cerium oxide nanoabrasives

[0138] .

[0139] Different epoxy carboxylic acid molecular structures affect the chemical properties of the cerium oxide surface, thereby changing the interaction between the particles and SiO2. Some epoxy carboxylic acids may increase the friction or reactivity between cerium oxide and the material surface, increasing the material removal rate; while others may reduce active sites or reduce the interaction between particles and materials, resulting in a decrease in polishing rate.

[0140] It can be seen from the experimental data in this experimental example that the present invention can increase the suspension stability of the polishing liquid while stabilizing the polishing rate, which is a significant technical advancement.

[0141] Experimental Example 2: Determination of suspension stability after long-term placement

[0142] The same mass of the modified epoxy-cerium oxide abrasive prepared in Example 1 and the commercially available common cerium oxide abrasive were prepared into a polishing liquid with a solid content of 10%. The prepared polishing liquid was left to stand in the laboratory, and images were recorded after standing for 1 hour, 7 days, 15 days and 30 days. The experimental results are shown in the figure. Figure 5-Figure 8 As shown in the figure, it can be seen that the polishing liquid prepared by the present invention can be stably suspended for 30 days without precipitation and aggregation; while the commercially available polishing liquid has obvious precipitation after being left to stand for 7 days, and the solution is completely clear after 15 days, and the liquid and solid are separated.

[0143] In the test of the experimental example, the solid content is generally selected to be 0.5%-10% for measurement. The present invention can maintain the suspension stability under the extreme condition of 10% solid content; thus, it can be seen that the polishing liquid prepared by the present invention can be stored stably for a long time, and the experiment proves that its suspension (D50) is up to 2 months.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A modified epoxy-cerium oxide polishing liquid, characterized in that: In terms of mass percentage, it is mainly made from the following raw materials: Modified cerium oxide abrasive 0.2%-0.5%; Stabilizer 0.02%-0.35%; Ammonia 0.25%-0.40%; Deionized water 99.08%-99.2%; Wherein, the modified cerium oxide abrasive is a mixture of cerium oxide and epoxy carboxylic acid in a mass ratio of (20:1) to (200:1); The pH value of the modified epoxy-cerium oxide polishing liquid is 10-12; The epoxy carboxylic acid is cis-epoxysuccinic acid, 2,3-ethylene oxide dicarboxylic acid or, The epoxycarboxylic acid is a mixture of cis-epoxysuccinic acid and epoxyethylcarboxylic acid in a mass ratio of 1:1 or 0.5:

1.

2. The modified epoxy-cerium oxide polishing liquid according to claim 1, characterized in that: The mass ratio of the cerium oxide to the epoxy carboxylic acid is (40:1)-(100:1).

3. The modified epoxy-cerium oxide polishing liquid according to claim 2, characterized in that: The mass ratio of the cerium oxide to the epoxy carboxylic acid is 100:1 or 50:

1.

4. The modified epoxy-cerium oxide polishing liquid according to claim 1, characterized in that: The particle size of the cerium oxide is 200nm-400nm.

5. The modified epoxy-cerium oxide polishing liquid according to claim 1, characterized in that: The stabilizer is a mixture of one or more of polyvinyl alcohol, polyethylene glycol, polydimethylsiloxane, polyethylene oxide, polypropylene oxide, carboxymethyl cellulose, sodium polyacrylate or hydroxyethyl methyl cellulose.

6. The modified epoxy-cerium oxide polishing liquid according to claim 5, characterized in that: The stabilizer is polyvinyl alcohol, polydimethylsiloxane and carboxymethyl cellulose mixed in a mass ratio of (1-3): 1:

1.

7. The modified epoxy-cerium oxide polishing liquid according to claim 6, characterized in that: The stabilizer is a mixture of polyvinyl alcohol, polydimethylsiloxane and carboxymethyl cellulose in a mass ratio of 2:1:

1.

8. A method for preparing the modified epoxy-cerium oxide polishing liquid according to any one of claims 1 to 7, characterized in that: The steps include: preparing cerium oxide, and mixing the cerium oxide with deionized water to form a uniform slurry; Grinding the slurry to obtain a grinding medium, and freeze-drying the grinding medium to obtain a cerium oxide abrasive; The polishing abrasive is dispersed in deionized water, subjected to ultrasonic vibration, epoxy carboxylic acid is added, mixed and heated to 70°C-100°C for 12 hours, centrifuged, washed and freeze-dried to obtain a modified epoxy-cerium oxide abrasive; The epoxy-cerium oxide abrasive is mixed with deionized water, a pH regulator and a stabilizer are added, and ultrasonic dispersion is performed to obtain the abrasive.

9. The method for preparing the modified epoxy-cerium oxide polishing liquid according to claim 8, characterized in that: The freeze drying temperature is -30°C to (-20°C); The heating temperature is 80°C.

Citation Information

Patent Citations

  • Solidified abrasive lapping polishing pad having self-modifying function and preparation method

    CN101096080A

  • KR20220157327A

Cited By

  • A polishing liquid containing low-crystallinity CeO2 nanoparticles and a method for preparing the same

    CN122810714A